2000
DOI: 10.1093/oxfordjournals.molbev.a026365
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Diversity Correlated with Ecological-Edaphic and Genetic Factors in Three Microsites of Wild Emmer Wheat in North Israel

Abstract: This study was conducted to test the effects of internal (genetic) and external factors on allelic diversity at 27 dinucleotide microsatellite (simple sequence repeat [SSR]) loci in three Israeli natural populations of Triticum dicoccoides from Ammiad, Tabigha, and Yehudiyya, north of the Sea of Galilee. The results demonstrated that SSR diversity is correlated with the interaction of ecological and genetic factors. Genetic factors, including genome (A vs. B), chromosome, motif, and locus, affected average rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
2
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 55 publications
10
78
2
6
Order By: Relevance
“…Furthermore, Stephan and Cho (27) suggest that natural selection plays an essential role in controlling the length of a repeat. It was also shown that stress, e.g., edaphic stress, increases replication error (9,11). The many new alleles observed at ME2 suggest that this locus is particularly prone to accelerated evolution, perhaps due to a combination of factors, which may include stress, different edaphic factors (soil in Australia is ameliorated with lime to attain pH 8), or gene targets of selection that may be linked to this locus.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Stephan and Cho (27) suggest that natural selection plays an essential role in controlling the length of a repeat. It was also shown that stress, e.g., edaphic stress, increases replication error (9,11). The many new alleles observed at ME2 suggest that this locus is particularly prone to accelerated evolution, perhaps due to a combination of factors, which may include stress, different edaphic factors (soil in Australia is ameliorated with lime to attain pH 8), or gene targets of selection that may be linked to this locus.…”
Section: Resultsmentioning
confidence: 99%
“…However, asymmetrical gene flow has been reported to occur where peripheral populations meet at range boundaries (Cicero 2004;Grant et al 2004) and can be maintained without affecting selective forces on adaptive quantitative traits, including phenotypic variation (Sandoval 1994;Ross and Keller 1995;Hedrick 1999 ;Haavie et al 2000;Andersson et al 2004;Jordan et al 2005). In addition, although a correlation between patterns of diversity at neutral loci and differences in life-history traits has been reported (Stephan and Cho 1994;Kashi et al 1997;Li et al 2000;Turpeinen et al 2001), empirical investigations on neutral markers as indicators of genetic variation relevant to evolutionary potentials and population persistence are still scarce (Pearman 2001). Further studies employing variable, functional genes (Ford 2002) and a comprehensive set of phenotypic data (Hoekstra et al 2004) may recover additional information on genotypic and morphological diversity in southern Isabela and therefore help direct conservation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Although causing factors for these "non-random" mutations and/or selection are not known to this end, it is conceivable that heterogeneous environmental conditions among the localities might have played a role. For example, intensive studies in another wild barley species, H. spontaneum (Baek et al 2003;Dawson et al 1993;Nevo et al 2001;Turpeinen et al 2001), and in wild wheat, Triticum dicoccoides (Fahima et al 2002;Li et al 2000Li et al , 2002, have demonstrated that local or regional microscale differences in edaphic and climatic conditions may constitute effective selection constraints on genomic structure and function. In our case, although there should be no difference in climatic factors in those areas wherein the H. brevisubulatum plants were collected, it is possible that the edaphic conditions can be variable due to severity of salinity/alkaline content and/or degree of dryness (Guo et al 1998).…”
Section: Discussionmentioning
confidence: 99%